Preliminary studies of the ionospheric effect from the ionospheric regions using GPS permanent tracking stations - Z., Othman; W.A., Wan Abdul Aziz; M.T., Roslina (Universiti Teknologi Malaysia, 2002)
The Global Positioning System signals must travel through the earth's ionosphere on their way to GPS receivers on or near the earth's surface. The ionosphere is a shell of electron, and electrically charged atoms and molecules that surround the earth, stretching from a height of about 50 km to more than 1000 km above the earth's surface. When the GPS signals propagate through the ionosphere, they suffer an extra time delay as a result of their encounter with the free electrons. This time delay is determined by the density of electrons, which is characterised by the number of electrons in a vertical column with a cross-sectional area of one square metre. This number is called the Total Electron Content (TEe). The dispersive nature of the ionosphere makes it possible to measure its TEC using dual-frequency GPS observations collected by permanent GPS network. Therefore, the main objective of the experiment is to estimate the TEC values from dual-frequency GPS observables with respect to the characteristics of the ionospheric layers. Here, we have used carrier phase observations data from four station of the Malaysian GPS Active System (MASS), namely UiTM Arau, Bukit Pak Apil Kuala Terengganu, UTM Johor and USM, Penang to derive regional TEC values by using the Bernese softwares. The results have shown that approximately 0.5 - 0.6 TECU in TIDs Indicator Value for Peninsular Malaysia. This ionospheric information can be used for environmental studies (e.g. continuous weather monitoring and climatology), microwave communication signals and other geoscience applications